1984
DOI: 10.1017/s0022172400060976
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the use of pock size on the chorioallantoic membrane of fertile hen's eggs as a method of typing herpes simplex viruses

Abstract: SUMMARYOne hundred and eighteen herpes simplex virus isolates were typed in a 'diagnostic virology laboratory using their standard procedure by pock size on the chorioallantoic membranes (CAMs) of fertile hen's eggs. Forty-three were typed as type 1 and 75 as type 2. The isolates were then sent to a research laboratory in which they were typed blind, with or without subsequent passage in tissue culture, by neutralization with type-specific antisera. Discrepant results were found with only two isolates. The iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…This was probably because the work was done with high passage laboratory strains rather than low passage clinical isolates, since repeated passage of HSV isolates tend to diminish the distinctive properties of the two types by means of selection and mutation. Another study from the UK which had adopted HSV isolates by egg passage first reported that the size of pocks produced by HSV-2 were 0.8-1 mm, while HSV-1 were 0.2-0.5mm 18 , which is comparable to our findings. Similarly, other studies to differentiate HSV isolates from clinical samples by pock size observed that pocks produced by HSV-2 isolates were comparatively larger (>0.5 mm) while HSV-1 were smaller (<0.5mm) 15,17 .…”
Section: Discussionsupporting
confidence: 91%
“…This was probably because the work was done with high passage laboratory strains rather than low passage clinical isolates, since repeated passage of HSV isolates tend to diminish the distinctive properties of the two types by means of selection and mutation. Another study from the UK which had adopted HSV isolates by egg passage first reported that the size of pocks produced by HSV-2 were 0.8-1 mm, while HSV-1 were 0.2-0.5mm 18 , which is comparable to our findings. Similarly, other studies to differentiate HSV isolates from clinical samples by pock size observed that pocks produced by HSV-2 isolates were comparatively larger (>0.5 mm) while HSV-1 were smaller (<0.5mm) 15,17 .…”
Section: Discussionsupporting
confidence: 91%